MATHEMATICAL STUDY OF WEIGHTED TWO PARAMETERS EXPONENTIAL DISTRIBUTION - Mizaal, Awatif Rzzoky (MAGISTRA, 2015)
This paper deals with studying a weighted exponential distribution with two parameters ( )shape parameter ( ) and ( ) scale parameter ( ), and deriving itâs cumulative distribution function,reliability function, also deriving the estimators by maximum likelihood method and moment estimator which arefound after deriving the moment generating function and obtaining . Also we try to use twoparameters ( ) as well as the reliability function using different sample size ( ),comparison has been done using mean square error, all results explained by tables.Keywords: Weighted exponential distribution, scale and shape parameters, cumulative distribution function,reliability function, MLE, MOM.